Sistema de informações sobre a febre aftosa em bovinos no Estado de Minas Gerais - Joao Paulo Amaral Haddad (1997)
The thesis had as its main objective to develop and to apply a methodology using new techniques of informatics and statistical analysis in a specific study of animal health. Two complementery plamting approaches were used: the first was more descriptive and it adapted multimedia analytical techniques to have as result na information system for foot and mouth disease in cattle raising in the State of Minas Gerais. The other approach used a methodology of multidimensional data-specifically, the technique of factor analysis , of principal components; its purpose was to describe the relationships between socioeconomic variables and agricultural and livestock production in the municipalities of Minas Gerais. distinguishing among those that had, and those that had not, notified disease outbreaks in 1992-1995, A system was developed in MS Visual Basic 3.0 for Windows, incorporating a series of infomation, including: database for 880 outbreaks of notified foot and mouth disease, in the period fiom january 1992 to december 1995, for the 722 municipalities of the State; a bibliography about this disease, laws, decrees and norms related to its control, two reviews ofthe literature about the disease, extracted from the more important books and compendiums available, graphics illustrating relevant information about foot and mouth disease erradication, a carthographic animation, organized with the location of the outbrakes on a fortnight basis, enphasizing the dynamics of time and space spheres, maps with the location of outbrakes for every specific forthnigth or year, in a individual basis, images relative to foot and mouth disease, and, finally, the results of 12 factor analysis of principal components. The statistical analysis worked out shows important differences between municipalities having the disease and those not having the disease. The main and most evident phenomenan observed was that those Minas Gerais municipalities having outbreaks of the disease, in the period 1992-1995, had a higher economic and social development when compared to those not having the disease. The proposed methodologies in the present thesis demonstrated to be efficient and viable in the analysis of animal health problems, indicating new perspectives for studies in Veterinary Epidemiology.